Microstructure, Mechanical and Thermal Properties of Mg-0.5Ca-xZr Alloys - Ying-Long Zhou; Jie Liu; Dong-Mei Luo (Crystals, 2022)
To evaluate the potential values in heat dissipation applications, this study investigated the microstructure, mechanical and thermal properties of the Mg-0.5Ca-xZr alloys (x = 0.5 and 1 wt.%) under the as-cast, as-extruded and aged states. The phase constituents of the Mg alloys were examined by X-ray diffraction analysis, and the microstructure was inspected by optical microscopy and scanning electron microscopy. The thermal conductivity and mechanical properties of the Mg alloys were measured by the laser flash method and tensile tests, respectively. The results showed that the Mg alloys exhibited the equiaxed microstructure which is composed of α-Mg, Zr and compound Mg2Ca. Both the extrusion process and increase of Zr content remarkably enhanced the mechanical strength of the Mg alloys and deteriorated the thermal performance simultaneously. It was also found that the thermal conductivity and mechanical strength of the Mg alloys increased gradually with the increase of aging time due to the higher precipitation of Zr and compound Mg2Ca during the aging treatment. TheMg-0.5Ca-0.5Zr alloy aged at 473 K for 48 h demonstratedhigher thermal conductivity than the required values of the Mg alloys used as heat dissipation materials. Moreover, theMg-0.5Ca-0.5Zr alloy exhibited similar mechanical strength to the commonly-used Mg alloys, highlighting its potential become a potential heat dissipation material in the future due to its good combination of high thermal performance and mechanical strength.